2007
DOI: 10.1111/j.1467-789x.2007.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Internet use for weight loss

Abstract: With rising rates of obesity and obesity-related health problems, finding additional means to help reduce obesity is critical. This review examined the impact of the Internet as a medium to deliver weight loss programs. Specifically, the review examined the public's interest, the availability and the known efficacy of Internet-based weight loss programs. Findings showed that the general public is turning to the Internet for diet and fitness information and has reported that information they found online has im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
94
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 21 publications
(53 reference statements)
4
94
0
2
Order By: Relevance
“…While a handful of narrative or systematic reviews 9,[32][33][34] and one meta-analysis 35 of computer-based interventions to assist in weight loss already exist, none has explicitly focused on evaluating the independent effect a computer delivery modality might have on the effectiveness of a weight loss intervention. To more closely address this objective, we conducted a systematic review and meta-analysis of randomized controlled trials comparing the effectiveness of computer-based interventions versus non-computer-based interventions for reducing weight or BMI among overweight and obese adults.…”
mentioning
confidence: 99%
“…While a handful of narrative or systematic reviews 9,[32][33][34] and one meta-analysis 35 of computer-based interventions to assist in weight loss already exist, none has explicitly focused on evaluating the independent effect a computer delivery modality might have on the effectiveness of a weight loss intervention. To more closely address this objective, we conducted a systematic review and meta-analysis of randomized controlled trials comparing the effectiveness of computer-based interventions versus non-computer-based interventions for reducing weight or BMI among overweight and obese adults.…”
mentioning
confidence: 99%
“…Recent systematic reviews highlight the potential of web-based treatments in achieving significant weight loss (5)(6)(7)(8) . However, they have also found that most studies fail to follow up participants beyond the intervention period (6) , so it is not known whether participants who successfully lose weight with web-based programmes can maintain the lost weight.…”
mentioning
confidence: 99%
“…Telecare can be carried out with tools such as web-sites, e-mail, chat lines, videoconference, telephone and mobile phones (Castelnuovo, Gaggioli, Mantovani, & Riva, 2003). As already indicated in several studies (Cline & Wong, 1999;Goulis, et al, 2004;Jeffery, et al, 2003;Maglaveras, et al, 2002;Rice, 2005) and in various reviews (Neve, Morgan, Jones, & Collins, 2009;Saperstein, Atkinson, & Gold, 2007;Weinstein, 2006), behavioral treatments delivered through the internet (web-site and e-mail) may be valid alternatives to reduce expensive and time-consuming clinical visits.…”
Section: Introductionmentioning
confidence: 99%